2016
DOI: 10.1093/mnras/stw2186
|View full text |Cite
|
Sign up to set email alerts
|

Radial variation in the stellar mass functions of star clusters

Abstract: A number of recent observational studies of Galactic globular clusters have measured the variation in the slope of a cluster's stellar mass function α with clustercentric distance r. In order to gather a deeper understanding of the information contained in such observations, we have explored the evolution of α(r) for star clusters with a variety of initial conditions using a large suite of N -body simulations. We have specifically studied how the time evolution of α(r) is affected by initial size, mass, binary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 60 publications
9
33
0
Order By: Relevance
“…So, the shorter the timescale of internal dynamical evolution the more efficient is the depletion of the MF. However, the location of N-body simulations in the log t rh − α plane is highly sensitive to the original slope of the IMF, with clusters starting with a steeper IMF reaching also steeper present-day MFs after a given number of elapsed relaxation times than clusters starting with flatter IMFs (Webb & Vesperini 2016). Thus, a significant spread in this relation would be apparent if cluster-to-cluster variations of the IMF were present at the epoch of their formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the shorter the timescale of internal dynamical evolution the more efficient is the depletion of the MF. However, the location of N-body simulations in the log t rh − α plane is highly sensitive to the original slope of the IMF, with clusters starting with a steeper IMF reaching also steeper present-day MFs after a given number of elapsed relaxation times than clusters starting with flatter IMFs (Webb & Vesperini 2016). Thus, a significant spread in this relation would be apparent if cluster-to-cluster variations of the IMF were present at the epoch of their formation.…”
Section: Discussionmentioning
confidence: 99%
“…Piotto & Zoccali 1999). On the theoretical side, many surveys of N-body simulations have been performed to investigate the evolution of the MF in GC-like objects (Vesperini & Heggie 1997;Baumgardt & Makino 2003;Lamers, Baumgardt & Gieles 2013;Webb & Vesperini 2014, 2016. In particular, Leigh et al (2012) used a set of N-body runs assuming different masses, concentrations, orbital eccentricities and tidal environments to reproduce the MFs of a sample of 27 Galactic GCs and showed that the natural evolution of a universal IMF could actually produce the observed cluster-to-cluster differences.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we do not include primordial mass segregation as its effects on the overall mass function evolution should be lost at later times, when clusters begin losing stars via tidal stripping (see Subsec. 3.5 of Webb & Vesperini 2016). The simulations include tidal forces, computed assuming that the clusters follow circular orbits in a point-mass galactic gravitational field (see Trenti et al 2007a for details), underfilling the tidal radius by a factor of 3.…”
Section: Numerical Frameworkmentioning
confidence: 99%
“…Primordial mass segregation also affects the dynamical evolution of a cluster through stellar evolutionary mass loss of the massive stars. Initial mass segregation may also lead to a different evolution of the radial dependence of the stellar mass function in the evolving star cluster when compared to a cluster not initially mass segregated (Webb & Vesperini 2016).…”
Section: Introductionmentioning
confidence: 99%